The Transformation of Jakarta's Administrative Status, 1905-1964: From Gemeente Batavia to Special Capital Region - Tomy Wijaya; Syafruddin Yusuf (MASI Mandiri Edukasi, 2026)
This study examines the historical progression of Jakarta's administrative classification from Gemeente Batavia (1905) to the Special Capital Region (DKI) in 1964. This study analyzes the impact of colonial heritage, the Japanese occupation, and post-independence political dynamics on Jakarta's evolution from a colonial city to a national capital with a unique administrative identity. The employed methodology is the historical method, which includes the stages of heuristics, source criticism, interpretation, and historiography. This study uses a historical institutionalism framework to analyze the continuity and institutional transformation (path dependency) within Jakarta's government. The study's findings reveal that the Gemeente Batavia period (1905-1942) instituted a modern municipal governance framework under colonial supervision; the Japanese occupation (1942-1945) intensified centralization and solidified the identity of